Adolescent Pregnancy the Case of Wa West District in Upper West Region of Ghana - Vengkungmene, Clifford; Kor, Jacob Aaworb-nang Maabobr (Advances in Social Sciences Research Journal, 2022)
Adolescence is the phase of life between childhood and adulthood from ages 10 – 19 years. This age category is further divided into sub categories as Early (10 – 14years) adolescent and late (15 – 19years) adolescent. It is a very unique stage of human development and an important time for laying the foundation for good health. All the vices emanates from this stage of life if not managed well. This is the stage where there is rapid physical, cognitive and psychosocial development. Adolescents constitute a significant proportion of our population (about 21.9%) [AHSPS 2016-2020]. A cross sectional descriptive design was used in this study where data was collected at a point in time across the health facilities with Reproductive and Maternal Health Services. Both quantitative and qualitative methods of data collection were used to have a fair assessment of the issues. This study design was adopted as most appropriate because it offered the researchers the opportunity to delve deeply into the issues and appropriately respond to the objectives. The principal respondents were the pregnant Adolescent girls and adolescent girls that delivered in 2021 who had contact with health service providers within the year. Health facilities that provide Reproductive Health Services were purposively sampled from 9 Health Centres and 13 CHPS compounds. In total 390 pregnant adolescent girls who were either pregnant or lactating were studied. The secondary respondents were parents of the pregnant adolescents and lactating girls, staff of Ghana Education Service as well as department of social welfare who were purposefully selected because of the critical role they play in adolescent health related issues. The number of adolescent pregnancies by age category, early adolescence (10 – 14years) and late adolescence (15 – 19years). The late adolescent recorded the highest number of pregnancies (N=383, 98.2%) and seven (7) pregnancies occurred within the early adolescent category with the youngest adolescent being 13years.